2001
DOI: 10.1046/j.1365-2788.2001.00373.x
|View full text |Cite
|
Sign up to set email alerts
|

Mental disorder in adults with intellectual disability. 2: The rate of behaviour disorders among a community‐based population aged between 16 and 64 years

Abstract: Despite the difficulty of defining behaviour disorder, most previous studies have reported a high rate of behaviour disorders in people with intellectual disability (ID). The aim of the present study was to establish the overall rate and types of behaviour disorders in a population-based sample of adults with ID. The other aim was to explore the possible risk factors that are associated with the overall rate as well as different types of behaviour disorders. One hundred and one adults with ID aged between  a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

8
151
4
6

Year Published

2003
2003
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 205 publications
(169 citation statements)
references
References 19 publications
8
151
4
6
Order By: Relevance
“…The rate of PBs in people with ID is high (5) and their presentation is determined by many complex factors. The pathogenic contribution of organic conditions, psychiatric disorders, environmental influences, or a combination of these has to be carefully established for every single case.…”
mentioning
confidence: 99%
“…The rate of PBs in people with ID is high (5) and their presentation is determined by many complex factors. The pathogenic contribution of organic conditions, psychiatric disorders, environmental influences, or a combination of these has to be carefully established for every single case.…”
mentioning
confidence: 99%
“…On the other hand, some authors suggested that a low IQ excludes the pre sence of psychiatric dis orders [2], considering intellectual disability and psychiatric disorders as being mutually exclusive [3]. Other authors believed that persons with intellectual disability are protected from certain psychological stress and therefore are less prone to develop psychiatric illness [4]. Today, psychiatric disorders are considered as being linked to intellectual disability.…”
Section: Introductionmentioning
confidence: 99%
“…Actual estimates of co-morbidity of learning disability and psychiatric illness have ranged across studies from 10% to 39%, 3 but all are significantly higher than the general population and the prevalence of behaviour disorders (which often reflect psychiatric disorder in this group) has been found to be even higher at 60.4%. 4 The World Health Organisation, 5 in its definition of learning disability, points to the importance of holistic approaches to understanding individual needs; however there is still a tendency to attribute much emotional distress experienced by an individual to the disability rather than to particular emotional needs or psychiatric disorder.Over the last 20 years many changes have taken place in the development of care and services for people with learning disabilities. The philosophies of normalisation 6 and inclusion have brought about a change in focus for these services, with more emphasis on individual characteristics and needs than disabilities, so that even people with severe problems are seen as having a right to be supported in community settings.…”
mentioning
confidence: 99%
“…Actual estimates of co-morbidity of learning disability and psychiatric illness have ranged across studies from 10% to 39%, 3 but all are significantly higher than the general population and the prevalence of behaviour disorders (which often reflect psychiatric disorder in this group) has been found to be even higher at 60.4%. 4 The World Health Organisation, 5 in its definition of learning disability, points to the importance of holistic approaches to understanding individual needs; however there is still a tendency to attribute much emotional distress experienced by an individual to the disability rather than to particular emotional needs or psychiatric disorder.…”
mentioning
confidence: 99%
See 1 more Smart Citation